Pendekatan Tata Ruang dalam Pengendalian Daerah Sempadan Sungai sebagai Area Resapan Banjir di Desa Beleka Lombok Tengah - Muttaqin, Muttaqin; Farah, Ayuni; Muzaki, Ivan (Journal of Community Development and Empowerment, 2025)
Beleka Village, located in Central Lombok Regency, is an area with a high vulnerability to flood disasters, particularly around the riverbank buffer zones. This issue is exacerbated by land-use changes and the low public awareness of the importance of maintaining the ecological function of riverbank areas as water infiltration zones. This community service activity aims to educate the public and provide adaptive and sustainable spatial planning recommendations as part of flood control efforts. The approach used is participatory, involving outreach activities, participatory mapping, and focus group discussions (FGDs) with residents, community leaders, and village government officials. The results of the activity show that spatial planning approaches can improve community understanding of the strategic function of riverbanks and encourage the formation of local agreements to protect and rehabilitate these areas as conservation and flood infiltration zones. In addition, a draft spatial utilization plan was produced, based on disaster mitigation principles that integrate local wisdom and ecological aspects. This activity highlights the importance of synergy between scientific approaches and community participation in sustainable spatial management at the village level. It is hoped that this initiative can serve as a replicable model for other villages facing similar challenges, particularly in the context of flood control through spatial planning.